THERMOTHERAPY IN THE CONTROL OF Fusarium spp. IN ANGICO SEEDS [Anadenanthera colubrina (Vell.) Brenan] AND MAINTENANCE OF PHYSIOLOGICAL QUALITY - de Medeiros, José George Ferreira; da Silva, Edcarlos Camilo; da Silva, Hilderlande Florêncio; Gomes, Rommel dos Santos Siqueira; do Nascimento, Luciana Cordeiro (Floresta, 2023)
Thermal treatment is frequently used to overcome dormancy in forest seeds; however, it can also be used to control seed-born pathogens. This study aimed to evaluate the efficiency of thermotherapy in controlling Fusarium sp. in angico seeds [Anadenanthera colubrina (Vell.) Brenan] collected in the state of Paraíba, Brazil, and its effect on physiological quality. Nine seed sources located in the municipalities of São João do Cariri - PB, Boa Vista - PB, and Sumé - PB were selected for this study. For the sanitary test, the treatments were composed of untreated seeds (control), chemical treatment, and thermal treatment at temperatures of 50, 60, and 70 °C immersed for 10, 20, 30, and 40 minutes. The same treatments were used in the germination test, and the percentage of germination, first count, dead seeds, seedling length, and germination speed index were evaluated. The results showed that the thermal treatments effectively reduced Fusarium sp. in the seeds. Thermotherapy did not negatively affect the physiological quality of angico seeds and led to an increase in germination percentage.